1984
DOI: 10.1021/bi00321a087
|View full text |Cite
|
Sign up to set email alerts
|

Activation of transglutaminase during embryonic development

Abstract: Incorporation of [3H]putrescine into proteins was shown to increase markedly in sea urchin eggs upon fertilization. Emetine, an inhibitor of protein synthesis, had no effect on the rate of protein labeling. However, the reaction could be prevented by the addition of 2-[3-(diallylamino)-propionyl]benzothiophene, a noncompetitive inhibitor of transglutaminase, and also by dansylcadaverine, which is a substrate for transglutaminase. The inert N alpha-dimethyl analogue of dansylcadaverine had no influence. Conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…To the dried precipitate, 0.5 ml of 0.1 M ammonium bicarbonate and a small crystal of thymol were added. Enzymatic digestion was carried out by the procedure of Cariello et al (11) with the sequential addition of subtilisin (10 jig and 4 pug), pronase (10 Ag and 4 pug), carboxypeptidase Y (5 ,tg), leucine aminopeptidase and prolidase (2 pug each), and, again, leucine aminopeptidase (2 pkg). The samples were dried and dissolved in 0.2 ml of water, and amino acid analysis was performed according to the o-phthalaldehyde derivatization procedure of Griffin et al (12).…”
Section: Methodsmentioning
confidence: 99%
“…To the dried precipitate, 0.5 ml of 0.1 M ammonium bicarbonate and a small crystal of thymol were added. Enzymatic digestion was carried out by the procedure of Cariello et al (11) with the sequential addition of subtilisin (10 jig and 4 pug), pronase (10 Ag and 4 pug), carboxypeptidase Y (5 ,tg), leucine aminopeptidase and prolidase (2 pug each), and, again, leucine aminopeptidase (2 pkg). The samples were dried and dissolved in 0.2 ml of water, and amino acid analysis was performed according to the o-phthalaldehyde derivatization procedure of Griffin et al (12).…”
Section: Methodsmentioning
confidence: 99%
“…Peroxidase-mediated tyrosine-tyrosine cross-links are involved in the hardening of the sea urchin fertilization membrane (6,13), and a variety of cross-links involving lysine oxidase are present in collagen (10,35).…”
mentioning
confidence: 99%
“…Comparable studies in sea urchin embryos reported incorporation of 18.2 pmol of putrescine equivalents per g of protein (15 (19).…”
mentioning
confidence: 87%
“…The possibility that dansylcadaverine interferes with cell uptake of spermidine might be considered. In this regard, however, it is worth noting that recent studies of sea urchin (Arbacia) embryogenesis proved conclusively that posttranslational modification of protein by the polyamine putrescine is mediated by transglutaminase (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation